2016
DOI: 10.1080/10640266.2016.1153400
|View full text |Cite
|
Sign up to set email alerts
|

Parent-based prevention program for the children of mothers with eating disorders: Feasibility and preliminary outcomes

Abstract: The children of mothers with eating disorders are at high risk of feeding and eating problems and broader developmental difficulties. The Parent-Based Prevention (PBP) of eating disorders targets risk factors and facilitates behavioral change in parents to mitigate potentially negative outcomes of their children. This pre/post uncontrolled study evaluated the feasibility and preliminary outcomes of PBP. PBP was found to be a feasible intervention for mothers with eating disorders and their spouses, with satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Some programs for mothers with EDs and their toddlers delivered in a dyadic or parents‐group setting have been proposed (Bryant‐Waugh, Turner, Jones, & Gamble, ; Runfola et al., ; Stein, Woolley, Senior, et al, ) and produced an improvement in parental self‐efficacy and parenting competence. However, these programs mostly focused on mothers (for a comprehensive study considering the role of fathers, see Sadeh‐Sharvit, Zubery, Mankovski, Steiner, & Lock, ). Moreover, the results of this study have clinical implications because they demonstrated that parents with BED cannot be treated as a homogeneous group.…”
Section: Discussionmentioning
confidence: 99%
“…Some programs for mothers with EDs and their toddlers delivered in a dyadic or parents‐group setting have been proposed (Bryant‐Waugh, Turner, Jones, & Gamble, ; Runfola et al., ; Stein, Woolley, Senior, et al, ) and produced an improvement in parental self‐efficacy and parenting competence. However, these programs mostly focused on mothers (for a comprehensive study considering the role of fathers, see Sadeh‐Sharvit, Zubery, Mankovski, Steiner, & Lock, ). Moreover, the results of this study have clinical implications because they demonstrated that parents with BED cannot be treated as a homogeneous group.…”
Section: Discussionmentioning
confidence: 99%
“…Forty participants (43.48%) attended both sessions and completed posttest surveys. Despite a lower retention rate than desired for the posttest component, the sample in this study ( n = 40) is comparable and/or higher than samples found in similar research implementing psychoeducational prevention programs with parents using a one-group, uncontrolled, pretest–posttest design (Brown, 2016; Sadeh-Sharvit et al, 2016).…”
Section: Methodsmentioning
confidence: 61%
“…Parent‐Based Prevention following Bariatric Surgery targets key parental cognitions and behaviors associated with known risk factors for the development of obesity, including parental feeding practices as well as children’s eating behaviors, sleep habits, physical activity, and stress levels (Clark et al, 2007; Sadeh‐Sharvit & Lock, 2018; Sadeh‐Sharvit et al, 2016), while also preventing risk associated with eating disorders. As part of this process, the program works to reduce child exposure to maladaptive parental modeling of unhealthy eating patterns, appearance‐based comments, and weight bias on the family (Densham et al, 2017; Zuba & Warschburger, 2017).…”
Section: Pbp‐b Intervention Structure and Targetsmentioning
confidence: 99%